Incarnate - Meadows, Jodi.; Taub, Katherine ([S.l.] : Harperchildren's Audio, 2012)
Ana is new. For thousands of years in Range, a million souls have been reincarnated over and over, keeping their memories and experiences from previous lifetimes. When Ana was born, one of those souls vanished, and no one knows why. When Ana travels to the capital city of Heart, its citizens treat her as a nosoul, suspicious and afraid of what her presence means. When dragons and sylph attack the city, is Ana to blame? Ana needs to uncover the mistake that gave her someone else's life, but will her quest threaten the peace of Heart and destroy the promise of reincarnation for all?